Acute and subchronic toxicity study of the water extract from root of Citrus aurantifolia (Christm. et Panz.) Swingle in rats - Chunlaratthanaphorn S. (2014)
Acute and subchronic toxicities of the water extract from the roots of Citrus aurantifolia were studied in both male and female rats. Oral administration of the extract at a single dose of 5,000 mg/kg body weight (5 male, 5 female) did not produce signs of toxicity, behavioral changes, mortality or differences on gross appearance of internal organs. The subchronic toxicity was determined by oral feeding the test substance at the doses of 300, 600 and 1,200 mg/kg body weight for 90 days (10 male, 10 female). The examinations of signs, animal behavior and health monitoring showed no signs of abnormalities in the test groups as compared to the controls. The test and control groups (on the 90th day) and the satellite group (on the 118th day) were analyzed by measuring their final body and organ weights, taking necropsy, and examining hematological parameters, blood clinical chemistry and histopathology features. The oral administration of 1,200 mg/kg/ day of the extract of C. aurantifolia in male and female rats caused a significant increase in the liver enzymes, which remained within the normal range, but did not produce a significant histopathological change in the internal organs. In conclusion, the extract from the roots of C. aurantifolia administered orally did not cause acute or subchronic toxicities to male and female rats.